AEZ and Gherkin Production under Contract Farming in Karnataka - Chandrashekar, H.M. (Indian Journal of Marketing, 2008)
Gherkin (Cucumis sativus L.), is a cucurbitaceous vegetable crop of 90 days duration, which is harvested raw for pickling. The product has negligible domestic market and the cultivation is exclusively for exports. The preserved/pickled fruits are used in the preparations like sandwiches, pizzas, etc. Major destinations for its exports are Europe, USA, Russia, Australia and few other countries. The crop was introduced to India only in 1990 as the crop can be cultivated round the year unlike other major producing countries like Mexico, Hungary and Madagascar, where it can be cultivated only for three months in a year. Further, Gherkin is a labour-intensive crop, and, hence, the cost of cultivation is lower in labour surplus country like India compared to Europe and America. For this reason, industries engaged in marketing of gherkin abroad prefer to procure the produce from India.Contract farming can be defined as an agreement between farmers and processing and/or marketing firms for the production and supply of agricultural products under forward agreements, frequently at predetermined prices. It is a system of production wherein the purchaser, usually a company engaged in processing and/or marketing/exporting of agricultural commodities, provides production support to the farmers by supply of inputs and technical advice to produce an agricultural commodity in agreement of farmers giving back specific quantity and quality of the commodity at a predetermined time and price and the company under obligation to buy the same.